Energietransitie: omarm de complexiteit: Ontwikkeling en grootschalige toepassing van energieneutrale renovatieconcepten voor de naoorlogse sociale woningvoorraad - Stutvoet, Eefje (A+BE | Architecture and the Built Environment, 2018)
This book presents the outcome of research on conditions for development and large scale application of energy neutral renovation concepts, which can contribute to the transition towards an energy neutral post-war social housing stock. Two projects are studied of the innovation and transition program ‘Energy Leap’ (Energiesprong); ‘Slim & Snel’ and ‘De Stroomversnelling’. The aim of both projects was to stimulate the development and large scale application of energy efficient renovation concepts for the post-was serial built social housing stock. In doing so, they focus on product and process innovation, combined with industrialization, to make renovation concepts scalable and affordable. Background There is a large energy saving potential in the existing housing stock, which can contribute to a sustainable built environment. For decades people have been making homes more energy efficient. The current Dutch housing stock exist for one third of dwellings from the period 1945 till 1975 (Ministerie van Binnenlandse Zaken en Koninkrijkrelaties, 2016). Due to the large production of houses from housing associations at that time, a large percentage of their stock still consists of dwellings from this period. Post-war social rental housing is often in need of a major improvement, especially in the energy field. Agreements have been made within the social rental sector to bring the housing stock to average label B before 2021 (SER, 2013), as a step towards an energy neutral stock in 2050. However, the current pace of energetic improvements is still insufficient to achieve the objectives. A transition is needed. The slow transition to an energy-neutral housing stock can partly be explained by the existing structures and related ways of thinking and acting in construction. Housing associations are willing to make their property more energy efficient, but are limited by the deterioration of their financial position and the limitation of their duties in recent years. The ‘Energy Leap’ program, aimed at the realisation of an energy neutral built environment, tries to investigate, through experiments, where the system can be adjusted to make the transition. The transition path, or in other words the strategy to arrive at an energy neutral housing stock, which is used by Energy Leap, is the use of integrated renovation concepts that makes homes in one time energy neutral. Research objective and questions The objective of the research is to create insight into the conditions required for the development and large scale application of energy neutral renovation concepts. The research aims to contribute to the transition to an energy neutral post-war social housing stock. Based on this objective, the following main question has been formulated: Which conditions are required for the development and large scale application of energy neutral renovation concepts, which can contribute to the transition to an energy neutral post-war social housing stock? To answer this question, the activities of Energy Leap were studied that were focused on the post-war social housing stock. The first research question focuses on these activities of Energy Leap and the context in which they are undertaken. Subsequently, by conducting template analysis, actions are derived that contribute to the development and large scale application of energy neutral renovation concepts. By establishing links between the actions in relation to the transition, the researcher has come up with sets of coherent actions that relate to a specific part of the system. Based on these sets, the required conditions are formulated. 1. What activities have been undertaken from Energy Leap to accelerate the transition and in what context? a. Which activities were there in the Netherlands prior to Energy Leap for far-reaching energy savings in the existing housing stock? b. How is the Energy Leap program from which activities have been undertaken built up? c. On which theoretical concepts are the ideas of Energy Leap about the acceleration of the transition based? d. How are the activities of Energy Leap developed specifically for the development and large scale application of renovation concepts for the post-war social housing stock? 2. What actions can be distinguished from the activities of Energy Leap, which contribute to the development and large scale application of energy neutral renovation concepts? a. Which actions contribute to the development of energy neutral renovation concepts? b. Which actions contribute to the large scale application of the developed renovation concepts? c. What are the mutual relationships between these actions? 3. What conditions can be deduced from the determined actions and underlying theoretical concepts for the development and large scale application of energy neutral renovation concepts? Research approach For the research a pragmatic approach is used. The research can be typified as participative, observational and inductive. By conducting participatory and observational research within the Energy Leap program, activities of Energy Leap were explored and the data collection was done for the analysis. At the same time, desk research was carried out into the energy policy from the 1970s onwards and the theoretical concepts which Energy Leap is based. Based on these theoretical concepts, lessons have been drawn that can contribute to the transition and that were later used for the comparison between theory and practice. An inductive analysis, in the form of a template analysis, was carried out on the data that emerged from participatory and observational research, with which the actions were determined for development and large scale application of renovation concepts. The relations between the actions are also recorded. The lessons from the theory were compared with the activities of Energy Leap and the derived actions. From the insights that resulted from this, a schematic image was formed about the transition process. With this image a rearrangement has been made in the list of actions that contribute to development and large scale applications of renovation concepts. This distinguishes sets of interrelated actions that relate to a specific part of the system. From these sets the necessary conditions are derived for the development and large scale application of energy neutral renovation concepts, which can contribute to the transition to an energy neutral post-war social housing stock. Energy Leap: activities aimed at energy neutral renovation Energy leap can be seen as a transition program with which steps have been taken to start the transition to an energy neutral housing stock. Energy leap saw its own role mainly in to make a movement in the market and the realization of the necessary conditions. Energy leap focused on the development of integrated, affordable and scalable concepts. Using these it wanted to make ascending steps of 45%, to 60% and 80% energy reduction and it finally advocated bringing homes to Zero-On-The-Meter in one go. Energy leap helped parties achieve this by focusing on cooperation and knowledge sharing. Hereby it focused on the leaders in the market. At the same time, it tried to remove obstacles at all levels and to work on new approaches and solutions. Energy Leap has carried out various subprograms and projects with different approaches. There have been several tender projects supported by subsidy to create successful examples. Process support was provided to various projects, with the parties being guided in new ways of commissioning and integral cooperation. With a competition, a stage was given to innovative concepts. With deal making, agreements have been reached between parties to tackle large numbers of homes. Finally, knowledge products have been developed: tools for integral performance, financial feasibility and scaling up of concepts. Various theoretical approaches have influenced the Energy Leap program. Energy Leap has been set up as an implementation program for an innovation agenda. This innovation agenda has been drawn up from an innovation system approach (Hekkert et al., 2007). The philosophy of the Energy Leap program was based on the ideas of Transition Management (Rotmans, 2003). This has been applied by carrying out various transition experiments and by taking up the role of intermediary. The ‘Slim & Snel’ projects have been set up from the experimental idea, creating a protective environment and experimental space at project level (Van den Bosch, 2010). ‘De Stroomversnelling’ has much more the characteristics of Strategic Niche Management (Kemp et al., 1998). In addition, different views on development, change management and group processes have had an influence. Within the ‘Slim & Snel’ projects, but also at ‘De Stroomversnelling’, the lessons from the Soft System Methodology (Checkland en Poulter, 2006) have been deployed and various lessons from the Merger of Interests perspective (Van Hal, 2014) can be recognized. Theory U (Otto Scharmer, 2009) was used as inspiration for upscaling and for the target groups used was made of Rogers classifications (Rogers, 2003). Two subprograms of Energy Leap focused specifically on the post-war social housing stock, to which process support was given; ‘Slim & Snel’ and ‘De Stroomversnelling’. With Slim & Snel, Energy Leap strived for a series-based approach to accelerate the number of energy efficient housing renovations. In order to stimulate the development of integrated concepts, room for innovation has been created by using a different way of questioning and selection. Furthermore, it was required to work with multidisciplinary consortia that were coached in the cooperation in the chain to promote the integrality of the concepts. The scalability of concepts was pursued by looking for projects with similar houses from the sixties and the seventies. Within a project the aim was to renovate between four and five hundred homes, so that experience could be gained with a series-based approach. The initial intention was for several housing associations to jointly bring houses in a project in order to promote an snowball effect in the region. The plans that were made in the Slim & Snel projects were ultimately not scalable, partly due to the project based approach that the participants continued to keep. By focusing on innovation, integrality and scalability, the concepts also had to become affordable. The budgets that the housing associations had for the renovations were lower for each project, while the energy ambition went up. The idea also arose to realise a business case for the housing association by letting tenants pay housing costs (rent and energy costs) to the housing association. Unfortunately, legally and financially this was not yet possible within the existing frameworks. ‘De Stroomversnelling’ elaborated on the idea of realising affordable concepts by thinking in terms of the housing costs and the idea of realising a business case for housing associations. Also, much stronger efforts were made to arrive at scalable renovation concepts. The emphasis was on industrialisation and the realisation of building flows instead of working on a project basis. This was achieved by creating an even larger scale than was used for the ‘Slim & Snel’ projects. It is based on a deal in which agreements have been made for large numbers of houses in rapidly increasing steps; 1.000 in 2014, 11.000 in 2016 and 111.000 in 2020. This gave building parties the perspective with which they dared to invest in the development and design of an industrialised production process. By innovation the renovation was to be lowered in price and better suited to the wishes of the tenant. In order to realise a feasible business case for the housing association, the legislation has been adjusted so that from now on, in addition to the rent, they can also collect an energy performance fee for Zero-On-The-Meter houses. This cooperation agreement for ‘De Stroomversnelling’ was signed by four large construction companies and six housing associations. The intention was that during the duration of the agreement other housing associations could join in and the market would pick it up after the industrialisation phase and to realize 111.000 Zero-On-The-Meter dwellings. Actions that contribute to energy neutral renovation concepts In the analysis of the data, the improvements that Energy Leap tried to achieve were considered, as well as the obstacles they took away and the obstacles and opportunities they saw. A total of 78 possible actions were derived from this by the researcher for the development and large scale application of energy neutral renovation concepts, which have been subdivided into six main themes from the inductive analysis; supply and demand development, change amongst involved parties, support among residents, financing options, adjustment of institutional framework and transition management. Based on the main theme of supply and demand development, actions have been formulated for the query of the housing association and the development of renovation concepts. By putting an open request to the market and by combining the demands of similar projects, housing associations can provoke the development of renovation concepts using the request specifications. By simultaneously working on demand and supply development and ensuring openness between the parties involved about possible solutions, both the demand can be tightened and the supply improved. Set up the design process in such a way that the renovation solution can be designed integrally as one system. Make the process a precondition for innovation and provide process support to help avoid existing thinking and working patterns and help with the collaboration. Design a renovation solution in which the house can be made energy neutral, but which is also an integral solution for the overall quality so the lifespan is extended and the house once again meets the current and future housing needs. To this end, expand the scope outside the dwelling. Work on a scalable renovation concept that can be applied for a large number of houses, but can also fulfil the wish for customisation and diversity. As housing associations expand the scale so that a construction building party can set up a new production process. As a building party begin by prototyping to be able to test the renovation solution and the production process. Then industrialise the production process and work from building flows. As a housing association, use an open market approach in the tender process to give new parties and concepts a chance. Buy a renovation concept as a product. Ensure competition and select both on hard and soft values. As a construction company, do market research and pay attention to marketing in order to meet the needs of the housing association and market the developed renovation concepts. As building party, offer the renovation concepts with a performance guarantee. The main theme of change amongst involved parties relates to the role of the client and the contractor, the existing relationships with stakeholders, the cooperation and the change in the organisation. Actions aimed at the division of roles are: shift the design responsibility to the developing party, as a housing association transform to a purchasing company and service provider and as a construction company transform into a product company. Actions in the network of stakeholders are: involve new players for marketing and sales, involve (local) partners in the development, open up existing (supply) contracts and work on new services as an energy supplier. As a building company invest in your own innovation team. Cooperate integrally for the development of the concept and involve the entire chain. Cooperate on the basis of openness and equality. Changing roles means that new competencies are needed and policy and strategy must be adjusted. Actions to create support among residents relate to customer oriented work, communication and the use of the house. To this end, develop the renovation concept based on the resident’s needs and give the resident the opportunity to choose for himself by offering the renovation in a demand oriented manner. Work from a strong brand that appeals to residents. Make joint communications to the residents as housing association and building company. Use a differentiated residents approach to connect with different types of residents and locations. Make the renovation and communication about it as concrete and understandable as possible for residents. Make sure the living expenses for the resident do not increase after the renovation. As a construction party give the resident long term guarantees on the performance of the dwelling. Put these guarantees in a contract, check the production and installation process and monitor the performance during use. In the context of the main theme of financing options, actions are presented that relate to the financing by housing associations and the business case for the provider. Make sure the renovation becomes financially possible for the housing association by letting the money from the energy savings reach the housing association. For the financial assessment, consider the return over the lifespan instead of the initial investment. Ensure that there is a business case for the housing association at project level and ensure that financing can be obtained on the basis of the project returns. The business case of the construction party requires the pre-investment in the development of the renovation concept and setting up the production process. This expenditure is recovered by realising a large cost reduction on the realisation costs of the renovation and the creation of sufficient sales. The main theme of the institutional framework adjustment includes actions relating to legislation, regulations, permits and procedures. For the business case of the housing association, an important action is the amendment to allow the energy performance fee. Also, the current ‘netting arrangement’ (salderingsregeling) limits the financial feasibility. These limitations can be solved by allowing the energy production be netted at the building complex level and to provide certainty about the future of the current netting arrangement. Additionally, let small scale sustainable energy supplies fall under the Services of General Economic Interest (SGEI) and allow for self-sufficiency, because in the case of entirely sustainable production of energy in combination with storage, government regulated security of supply is not always necessary anymore. In the licensing process, the following actions can contribute to the use of renovation concepts: ensure uniform handling of permit applications, enable private quality assurance so that the renovation concept can be tested instead of a project, give a large scale exemption for (a part of) the environmental permit when standard extra measures are taken and provide room for experiments in the environmental permit. Under the main theme of transition control are actions to boost the previous actions and to accelerate the transition. The following actions have been formulated for this approach: steer the transition from a process-oriented approach, work simultaneously to realise the required conditions, set up an intermediary for the link between different levels, stimulate initiatives and test them in practical experiments and use a flexible approach that allows room for adaptation based on new insights. A transition is about long-term changes. Set a perspective for this and steer on an almost impossibly high ambition level to bring about change. At the beginning of the transition, focus on innovators and work with a small number of parties that can actually carry out innovation projects. At the same time, keep the government, umbrella organisations and supervisory parties informed of the ideas for a smooth course of the scale-up. Gradually scale up to larger and more complex situations and issues. Make the front runners ambassadors and ensure that other parties can catch on after the ‘pilot phase’. Provide visibility and awareness and allow the government to facilitate in the entire process. Finally, link the energy neutral renovations to other social goals and use time of ‘crisis’ to make a really big turnaround. Required conditions To derive the necessary conditions, the relationship between the actions in relation to the transition is considered. To this end, a picture of the transition process has first been formed by comparing the lessons from the theoretical concepts on which Energy Leap is founded against the activities of Energy Leap and the derived actions. With this representation of the transition process, events in the transition process are schematically plotted against scale and time. This schematic picture shows that the transition takes place at multiple levels – project, network, sector and society level – and that change at all levels is necessary to bring about the transition. In addition, a distinction has been made in this scheme between creating innovation space for the development of innovation on the one hand and building up the new system for large scale application on the other. The actions are placed in this image of the transition process. Eight sets of coherent actions have been formed by clustering these and making connections, from which the following conditions are derived: the presence of an experimentation space within which a number of parties jointly start, where new parties can join in and within which the parties can adapt; changing the role of housing associations, to view their property and finances differently, to purchase renovations and to mainly act as service providers to the resident; changing the role of construction parties to companies that independently develop products, produce them from an industrialised process and then offer them; the development of integral renovation products, in line with the market need, which are provided with performance guarantees; working from the resident’s needs and communication tailored to him / her; the development of profitable business cases for housing associations and construction parties, assuming no increase in housing costs for residents; changing regulations, providing certainty about incentive schemes and making existing regulations more flexible to create room for innovation and to amend existing regulations where they impede; effecting transition management with which the actors, the individual actions and the different scale levels are boosted and connected and with which the previous conditions can be realised and be maintained. Recommendations This research is based on the transition path that uses integrated renovation concepts which allow for housing to be made energy neutral in one go and can make the vast majority of the post-war social housing stock energy neutral by applying these concepts on a large scale. This is one of the possible routes that can make a major contribution. At the time of the conclusion of the research, the discussion about the reduction of natural gas in the Netherlands is taking place. This can cause both an acceleration in the transition, and the transition path explored here, as well as a start of new transition paths. Regardless of which route or routes are chosen, the study recommends that the link between short-term actions and transition-oriented work be continued. In practice, the research recommends that a protective environment be maintained for a longer time to allow energy neutral renovation concepts and the they require to come to maturity. The result of this research is a list of eight required conditions. This sounds very simple and clear. But it is a ’full package’; they are all needed. What this research has mainly shown is that it is complex. Everything is connected to everything else. Stand-alone measures won’t get the job done. That is precisely why it is a transition. It is about technology, and about money, and about residents who want to, and about a change among housing associations, and about change among builders, and about experimenting, and regulation and focus on short-term actions and long-term transition goals. The biggest recommendation from this study is: embrace this complexity.